Concentradores solares en Iberoamérica: una perspectiva para la educación en Colombia - Cabrera López, Steffany; Calvo Correa, Martha; Rodríguez, Diego (Revista Científica, 2011)
This research proposal was created with the objective of promoting educational activities that generate in communities with low coverage of potable water and energy, attitudes and actions that enable them to cope with the challenges they face. One way to solve this kind of problems is the use of solar energy as an energy source. Solar concentrator shave been widely deployed to provide potable water, energy for cooking, among others. We hoped that through the use of basic physical concepts of radiometry, communities take ownership of the solar concentrator technologies. For this purpose, we performed a literature review in the area of alternative energy in Latin America, focusing on educational technologies and used, in order to assess the relevance of repeating them in our context. Similarly statistically contrasted territories deficient in basic services, compared to regions of high solar energy, where were found the most relevant places to the use of such technological tools,which helps to remedy the short comings mentioned above.